Histological and histoquantitative study of the rat parotid gland after Trypanosoma cruzi infection - Silva R.C.; Cardoso J.E.; Silva G.A.B.; Moreira A.; Alves J.B. (Parasite, 2000)
The present study deals with the morphology of the rat parotid gland and its changes after Trypanosoma cruzi infection. The glands of control and infected animals were analyzed by histologic and histoquantitative methods. After 1 8 days of infection with T. cruzi, a significant reduction of the density of the volume of the acini and duct system, as well as a significant increase in the amount of connective tissue was noted. In addition, these animals displayed an increase in the number of cells undergoing mitosis. In the 45 day infected rats, there was return to the normal pattern. It is suggested that in the infected animals the decrease in body weight could be responsible for retarded sexual maturity, leading to the lower level of testosterone. It can be assumed that decreased levels of epidermal growth factor (EGF) and neural growth factor (NGF) caused by the lack of testosterone in infected animals also contribute to the atrophy of the parotid gland and to the proliferation of the connective tissue.